Comparison of Continuous 3-in-1 and Fascia Iliaca Compartment Blocks for Postoperative Analgesia: Feasibility, Catheter Migration, Distribution of Sensory Block, and Analgesic Efficacy. Issue 4 (1st July 2003) - Morau, Didier; Lopez, Sandrine; Biboulet, Philippe; Bernard, Nathalie; Amar, Julien; Capdevila, Xavier
Abstract : Background and Objectives: Efficacy and technical aspects of continuous 3-in-1 and fascia iliaca compartment blocks were compared. Methods: Forty-four patients scheduled for cruciate ligament repair or femur surgery were randomly divided into 2 groups. After surgery with the patient anesthetized, catheters were placed for continuous 3-in-1 blocks by means of a nerve stimulator (group 1). In group 2, the catheter was inserted for continuous fascia iliaca compartment block without the use of a nerve stimulator. In both groups, a 5-mg/kg bolus of 0.5% ropivacaine was administered followed by continuous infusion of 0.1 mL/kg/h of 0.2% ropivacaine for 48 hours. In the postoperative period, all the patients received parenteral propacetamol (6 g daily) and ketoprofen (200 mg daily) and 0.1 mg/kg of subcutaneous morphine as rescue analgesia if the visual analog scale (VAS) pain values were greater than 30 mm. We evaluated the technical difficulties relative to catheter placement, the location of the catheter, the analgesic efficacy, and the distribution of the sensory block at 1 hour, 24 hours, and 48 hours. Results: Catheter placement was faster in group 2, and the absence of nerve stimulation decreased material costs ( P < .05). No significant difference was observed between groups concerning location of the catheter tip under the fascia iliaca. In both groups, the distribution of the sensory block and its course were similar except for those of the obturator nerve (more sensory blocks in group 1, P < .05). No significant difference was noted between the groups regarding median VAS pain values and consumption of morphine during the 48-hour period. No major side effect was observed. Conclusions: The authors conclude that a catheter for continuous lumbar plexus block can be placed more quickly and at lesser cost using the fascia iliaca technique than the perivascular technique with equivalent postoperative analgesic efficacy.